Mild Endoplasmic Reticulum Stress Protects Against Lipopolysaccharide-Induced Astrocytic Activation and Blood-Brain Barrier Hyperpermeability - Wang, Yiwei; Chen, Yinan; Zhou, Qin; Xu, Jiawen; Qian, Qingqing; Ni, Pengfei; Qian, Yanning (Frontiers in Cellular Neuroscience, 2018)
Recent research has revealed that uncontrolled chronic neuroinflammation is closely associated with diverse neurodegenerative diseases, by impairing blood-brain barrier (BBB) function and astrocytic reaction. Endoplasmic reticulum (ER) stress is conventionally linked to the loss of neuronal structure and function and should be widely attenuated. This notion has been questioned by recent experimental studies, which have shown that nonharmful levels of ER stress had numerous beneficial roles against neurodegeneration, including neuroprotection and inhibition of cytokine production. Here, we investigated the mild ER stress-based regulation of LPS-induced inflammatory responses in astrocytes. Primary astrocytes were exposed to tunicamycin (TM), a compound that activates ER stress, with or without the ER-stress inhibitor sodium 4-phenylbutyrate (4-PBA) before LPS treatment. Astrocytic activation, proinflammatory factor production, and the extent of ER stress were assessed. In addition, the effect of mild ER stress on astrocytes and BBB function was determined in vivo. Male Sprague-Dawley rats received intracerebroventricular injections of TM with or without intraperitoneal 4-PBA before LPS administration. The levels of astrocytic activation and BBB permeability were measured after treatment. Our results showed that lower doses of TM resulted in a mild ER-stress response without inducing cytotoxicity and tissue toxicity. Nontoxic ER-stress preconditioning ameliorated LPS-induced overactivation and inflammatory responses in astrocytes. Moreover, pre-exposure to nonlethal doses of TM improved LPS-induced BBB impairment and cognitive ability dysfunction in rats. However, 4-PBA, reversed the protective effect of TM preconditioning in vitro and in vivo. We conclude that mild ER stress (“preconditioning”) can alleviate LPS-induced astrocytic activation and BBB disruption. Our findings provide a better understanding for the regulatory role of ER stress in neuroinflammation and indicate that mild ER stress might have therapeutic value for the treatment of neurodegenerative diseases.